2022
DOI: 10.3390/molecules27185946
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Phytochemical Composition and Antioxidant, Immunostimulant, and Hemolytic Activities of Nigella sativa (Ranunculaceae) and Lepidium sativum Seeds

Abstract: The Moroccan flora abounds and is an important reserve of medicinal plants. Nigella sativa and Lepidium sativum are plants that are widely used in traditional medicine for their multiple therapeutic properties. The current study aims to highlight the biological activities that can justify and valorize the use of these plants. Flavonoids, total phenols, condensed tannins, and sugars were determined. The biological activities tested were antioxidant by determining the IC50 (defined as the concentration of an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Phyto-haemagglution activity and haemagglutination limit test in the present study also revealed the toxicity caused by the extract by causing clumping of the cells. Phytolectins in the extract are majorly responsible for the clumping of erythrocytes which ultimately hinders the normal functioning of the cells (Senthilganesh et al 2021;Ouattar et al 2022). A similar kind of agglutination was also reported by Abdali et al (2021) while working on Linum usitatissimum extract.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Phyto-haemagglution activity and haemagglutination limit test in the present study also revealed the toxicity caused by the extract by causing clumping of the cells. Phytolectins in the extract are majorly responsible for the clumping of erythrocytes which ultimately hinders the normal functioning of the cells (Senthilganesh et al 2021;Ouattar et al 2022). A similar kind of agglutination was also reported by Abdali et al (2021) while working on Linum usitatissimum extract.…”
Section: Discussionsupporting
confidence: 60%
“…The test is based on the agglutination or precipitation of red blood cells caused by various toxic components present in the extract particularly lectins (Ouattar et al 2022). The assay was performed in a 96-well roundbottom plate as per the method described by Ouattar et al (2022).…”
Section: Phyto-haemagglution Activitymentioning
confidence: 99%
See 2 more Smart Citations
“… 20 , 21 Flavonoids, phenolics, alkaloids, saponins, glycosides, coumarins, fixed oils, proteins, vitamins, and minerals were found in L. sativum essential oil. 22 …”
Section: Introductionmentioning
confidence: 99%